Measuring the Alignment Gap Between Organizational Strategic Plans and Vision 2030 Goals: An Analytical Study in Saudi Arabia - Al-Lehyani, Badr Saleh; Tiwari, Alok Tiwari Ramadhar (Journal of Economic, Administrative and Legal Sciences, 2025)
This study aims to evaluate the alignment gap between current strategic plans and the objectives of Saudi Vision 2030. It examines the influence of alignment mechanisms on organizational performance and identifies key challenges that hinder effective strategic integration. A systematic literature review was conducted, integrating qualitative thematic analysis with basic quantitative frequency counts. Secondary data were collected from academic databases and government reports. In addition, a customized Vision Alignment Measurement Tool (VAMT) was developed, pilot-tested, and validated through expert reviews and exploratory factor analysis to ensure reliability and construct validity. The findings reveal significant misalignment between existing strategic initiatives and the Vision 2030 targets, primarily due to deficiencies in standardized KPIs, regulatory frameworks, and real-time monitoring systems. Evidence suggests that leadership commitment, enhanced stakeholder engagement, and adaptive planning are critical factors in closing these gaps. Effective strategic alignment requires the adoption of standardized evaluation tools, improved regulatory coherence, and dynamic performance monitoring systems. These measures are essential to mitigate misalignment, foster continuous improvement, and drive national transformation.
Keywords: Strategic alignment; Vision 2030; performance measurement; gap analysis; public policy